The intricate interplay between microglia and adult neurogenesis in Alzheimer’s disease - Früholz, Iris; Meyer-Luehmann, Melanie (Frontiers in Cellular Neuroscience, 2024)
Microglia, the resident immune cells of the central nervous system, play a crucial role in regulating adult neurogenesis and contribute significantly to the pathogenesis of Alzheimer's disease (AD). Under physiological conditions, microglia support and modulate neurogenesis through the secretion of neurotrophic factors, phagocytosis of apoptotic cells, and synaptic pruning, thereby promoting the proliferation, differentiation, and survival of neural progenitor cells (NPCs). However, in AD, microglial function becomes dysregulated, leading to chronic neuroinflammation and impaired neurogenesis. This review explores the intricate interplay between microglia and adult neurogenesis in health and AD, synthesizing recent findings to provide a comprehensive overview of the current understanding of microglia-mediated regulation of adult neurogenesis. Furthermore, it highlights the potential of microglia-targeted therapies to modulate neurogenesis and offers insights into potential avenues for developing novel therapeutic interventions.